ETERNAL: uma estratégia eficiente de tolerância a falhas utilizando memória não volátil - Gomes, Davi Braga (2019)
In-memory DBMSs have proven to be an efficient alternative for managing large volumes of data. They’re characterized by using RAM as their primary storage medium. However, such systems need nonvolatile storage to ensure the durability of its transactions. Byte addressable non-volatile memories (NVRAM) are ideal candidates for securing such a property because they have access times close to traditional RAM memory but still guarantee data persistence. In order to address the problem of transaction durability in main memory DBMSs, this paper proposes ETERNAL, a durability architecture that makes efficient use of nonvolatile memory, improving the process performance of persistence in such DBMSs. Experiments reveal that ETERNAL provides a higher throughput than the write-ahead logging (WAL) approach. It is also noteworthy that, even using nonvolatile memory as a storage medium, the WAL approach does not have a mechanism to deal with the scenario in which nonvolatile memory runs out.